Archaeological and Geophysical Evidence of a High-Energy Marine Event at the Phoenician Site of Cerro del Villar (Malaga, Spain). - Álvarez-Martí-Aguilar, Manuel; Suárez Padilla, José; Aubet, M.ª Eugenia; Machuca Prieto, Francisco; Martín Casado, Juan Manuel; Feist, Lisa; Val-Peón, Cristina; Reicherter, Klaus (Springer, 2022)
The Mediterranean coast of Spain, much of which is built-up and densely populated, is today a tourist hot spot. Additionally, there are vital infrastructures, including airports, harbours and industrial facilities along its coastal motorways. In comparison with the western and southern Atlantic coastlines, the region is relatively protected from storms, while earthquake-related inundations, namely, tsunamis, are also rare. The very imprecise historical and sedimentary record of a tsunami in 1522 near Almeria bear this out. However, new evidence is provided here for the oldest extreme wave event (EWE) affecting human settlements on the Iberian Peninsula. The Phoenician site of Cerro del Villar, located near the Andalusian city of Malaga, in the estuary of the river Guadalhorce, suffered two episodes of destructive flooding at the beginning and at the end of the seventh century BC. In this paper, the initial interpretation of the former as a fluvial flood is recovered, while the latter is reinterpreted as an extreme wave event of a possible tsunami.
Keywords: Maremotos - Málaga (Bahía) - Edad Antigua; Málaga (Provincia) - Restos arqueológicos; Geofísica en arqueología; Fenicios; Eventos de inundación extremos; Tsunami; Geoarqueología; Cerro del Villar, Málaga